Waist-to-Hip Ratio, Cardiovascular Outcomes, and Death in Peritoneal Dialysis Patients. (21st June 2010) - Su, Winnie S.; Clase, Catherine M.; Brimble, K. Scott; Margetts, Peter J.; Wilkieson, Trevor J.; Gangji, Azim S.
Abstract : Objectives . The primary objective of this study was to determine the relationship between waist-to-hip ratio (WHR), cardiovascular (CV) events, and mortality in peritoneal dialysis (PD) patients. A secondary objective was to investigate the association between abdominal obesity and systemic inflammatory markers. Methods . This is a prospective study of 22 prevalent PD patients. WHR was measured at baseline. C-reactive protein (CRP), tumour necrosis factor-α (TNF-α ), and interleukin-6 (IL-6) were measured. Main outcomes were first CV event and death from all causes. Survival analysis was used to examine the relationship between anthropomorphic measures and clinical outcomes. Results . Mean follow-up period was 3.1 years. In Kaplan-Meier analysis, survival was lower in those with higher WHR (P = .002 ). In Cox regression, WHR independently predicted mortality and first CV event after adjustment for known ischemic heart disease (hazard ratio [HR] 1.17, confidence interval [CI] 1.05–1.30 for death; HR 1.13, CI 1.01–1.26 for CV event). WHR correlated with serum TNF-α (r = 0.45 ;P = .05 ). Conclusion . The results of this study suggest WHR may be a risk factor for increased CV events and mortality in PD patients. Abdominal obesity is also associated with inflammatory markers. Larger studies are warranted to confirm these findings.